Fenomena Narsisisme Religius Kolektif dan Ajaran Sufi sebagai Upaya Pengobatan dan Pencegahannya - Muhammad Naufal Waliyuddin (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
One example of collective religious narcissism phenomenon which could be found in this age is ISIS, an organization that is arrogant, feel the most right, superior, and devalues others. This article presented a theoretical framework of those narcissism phenomena in the contemporary age that mingled with the presence of social media, a virtual world, and the emergence of an interconnected global society. This research investigated the conceptual and empirical trajectory of how collective narcissism can infect religious groups which are then called collective religious narcissism. The further analysis discussed how Sufi teachings could potentially be applied as a neutralizing strategy (treatment) or preventing the destructive tendency of collective religious narcissism. This study used qualitative research methods through a literature study approach by investigating several previous relevant studies. The data analysis employed the social psychology perspective. The result of this research is that the term introduced by Sigmund Freud (narziβtisch) was developed by Robert Waelder to become “narcissistic personality”, then experienced Heinz Kohut’s specification as “narcissistic personality disorder” and was further expanded by Agnieszka Golec de Zavala to become “collective narcissism” which may manifest in the sphere of nationalism, ethnocentricism, to the realm of religion. Some of the characteristics of collective religious narcissism are feeling the group is superior, the kindest and the most impeccable, having extensive desire to be recognized, a lack of empathy, and a tendency to exploitative behavior. This phenomenon could be widely observed on social media, particularly regarding the contestation of truth claims. This will have impacts on social segregation, political polarization, and infectious hatred. The values of the Sufi teachings that are considered effective in reducing these negative potencies are muḥāsabah, al-ḥazm, tawāḍu’, and maḥabbah.